Nature‐Inspired Multifunctional Ligands: Focusing on Amyloid‐Based Molecular Mechanisms of Alzheimer's Disease. (26th October 2015) - Simoni, Elena; Serafini, Melania M.; Bartolini, Manuela; Caporaso, Roberta; Pinto, Antonella; Necchi, Daniela; Fiori, Jessica; Andrisano, Vincenza; Minarini, Anna; Lanni, Cristina; Rosini, Michela
Abstract: The amyloidogenic pathway is a prominent feature of Alzheimer's disease (AD). However, growing evidence suggests that a linear disease model based on β‐amyloid peptide (Aβ) alone is not likely to be realistic, which therefore calls for further investigations on the other actors involved in the play. The pro‐oxidant environment induced by Aβ in AD pathology is well established, and a correlation among Aβ, oxidative stress, and conformational changes in p53 has been suggested. In this study, we applied a multifunctional approach to identify allyl thioesters of variously substituted trans ‐cinnamic acids for which the pharmacological profile was strategically tuned by hydroxy substituents on the aromatic moiety. Indeed, only catechol derivative3 [( S )‐allyl ( E )‐3‐(3, 4‐dihydroxyphenyl)prop‐2‐enethioate] inhibited Aβ fibrilization. Conversely, albeit to different extents, all compounds were able to decrease the formation of reactive oxygen species in SH‐SY5Y neuroblastoma cells and to prevent alterations in the conformation of p53 and its activity mediated by soluble sub‐lethal concentrations of Aβ. This may support an involvement of oxidative stress in Aβ function, with p53 emerging as a potential mediator of their functional interplay. Abstract : Shedding light on Aβ : Nature‐inspired ligands1 –3 allow exploration of the molecular mechanisms potentially engaged in chronic β‐amyloid (Aβ) injuries. This study supports the involvement of oxidative stress in Aβ function, and p53 was found to emerge as a potential mediator of their functional interplay.